Sinus bradycardia treated by long-term atrial pacing - Clarke, Malcolm (1970)
A technique for long-term atrial pacing is described. It uses the system whereby power from an external pulse-generator (including battery) is transferred through the intact skin by inductive-coupling. Once installed, there is no requirement for further surgery to effect battery changes, and the patient can control his heart rate over a wide range to suit his needs. It is suggested that pacing by such means may offer a preferable alternative to drug therapy in the treatment of low cardiac output due to pathological sinus bradycardia. Two patients successfully treated in this way are reported.